“Setting Them Up for Success”: Including Youth on the Autism Spectrum in 4-H - McCormick, Carolyn E. B.; Peskova, Veronika; Morgan, Abby; Carlson, Emily; Mason, Rose A. (Frontiers in Psychiatry, 2022)
YYouth on the autism spectrum often face challenges accessing services in rural communities compared to those who live in higher resource areas. There is a particular need for services that support skills that will help youth transition to adulthood and future employment. 4-H is a national youth development program that is well-positioned to address the needs of youth on the autism spectrum; however, minimal empirical evidence exists about the implementation and effectiveness of inclusive practices in 4-H programs. The goal of this study was to better understand barriers to enrollment and to identify gaps in support for youth on the autism spectrum participating in 4-H. Twenty Extension Educators in Indiana participated in two focus groups. Thematic analysis of focus group transcripts identified barriers to enrollment including awareness of 4-H as an inclusive program and difficulties navigating 4-H culture. Our analysis identified themes related to new training content and delivery including a resource portfolio, communication, individualized accommodations, and working within the existing leadership training structure. Findings support the benefits of 4-H as a program that can promote life skills and personal development for youth on the autism spectrum but also highlight a significant need for additional training opportunities and resources to increase uptake and improve the implementation of inclusive practices.